Intriguing Interaction of Bacteriophage-Host Association: An Understanding in the Era of Omics - Parmar, Krupa M.; Gaikwad, Saurabh L.; Dhakephalkar, Prashant K.; Kothari, Ramesh; Singh, Ravindra Pal (Frontiers in Microbiology, 2017)
Innovations in next-generation sequencing technology have introduced new avenues in microbial studies through “omics” approaches. This technology has considerably augmented the knowledge of the microbial world without isolation prior to their identification. With an enormous volume of bacterial “omics” data, considerable attempts have been recently invested to improve an insight into virosphere. The interplay between bacteriophages and their host has created a significant influence on the biogeochemical cycles, microbial diversity, and bacterial population regulation. This review highlights various concepts such as genomics, transcriptomics, proteomics and metabolomics to infer the phylogenetic affiliation and function of bacteriophages and their impact on diverse microbial communities. Omics technologies illuminate the role of bacteriophage in an environment, the influences of phage proteins on the bacterial host and provide information about the genes important for interaction with bacteria. These investigations will reveal some of the novel phage bio-molecules and biomarkers which demand to be unveiled.